(untitled) (American Journal of Technology and Applied Sciences, 2024)
Traditional mechanical retention methods for restorative materials have largely been replaced by adhesive restorative techniques that prioritize tooth conservation. These bonding techniques facilitate more conservative tooth preparations, reducing the reliance on macromechanical retention and limiting the removal of unsupported enamel. With adhesives advancing rapidly in recent years, it is now an ideal time to evaluate the clinical effectiveness of modern adhesives. This article seeks to provide an updated, clear, and thorough classification of dentin bonding agents, emphasizing current products that aim to improve clinical performance.